RESTORATIF JUSTICE SEBAGAI ALTERNATIF PENYELESAIAN PERKARA TINDAK PIDANA ANAK, SESUAI DALAM UU SISTEM PERADILAN PIDANA ANAK - Anggara Dwi Putra (Musamus University, 2020)
Abstract Law enforcement is needed in order to provide a sense of justice to the community and prevent lawbreakers from committing criminal acts (recidivists) to lawbreakers. adult and child. Children are the younger generation who are the successors as a resource for achieving national development goals. In the Indonesian constitution, children have a strategic role that is explicitly stated that the State guarantees the right of every child to survival, growth and development and to protection from violence and discrimination. Diversion is done with the reason to provide an opportunity for lawbreakers to become good people again through non-formal channels by involving community resources, diversion seeks to provide justice for cases of children who have already committed a crime to the law enforcement officials as law enforcement parties. Keywords: Diversion, Out-of-Court Settlement, Children in Confront with the Law